A case of topical opioid‐induced delirium mistaken as behavioural and psychological symptoms of dementia in demented state. Issue 2 (12th June 2013) - Ito, Go; Kanemoto, Kousuke
Abstract In Japan, indications for opioid analgesics, once exclusively used as pain killers for patients suffering from malignant cancer, have been expanded for a wide range of pain. Herein we report a patient with opioid‐induced delirium associated with the administration of buprenorphine patches that was well below the indicated therapeutic range limit. An 82‐year‐old woman was referred to us from an orthopaedic practitioner for uncontrollable behavioural problems apparently caused by the beginning of dementia; the patient had gradually developed disorientation, visual hallucinations, and delusions. Laboratory and imaging findings excluded common causes of delirium including Alzheimer's disease and diffuse Lewy body disease. Detailed questioning revealed that the patient's confused state appeared following a buprenorphine patch dose increase and subsequently disappeared after administration was stopped. Delirium has not been reported as a side‐effect in clinical trials of buprenorphine patches. However, our findings in this case show that even topical opioids can precipitate the development of a delirious state in elderly patients.